Note onset detection in musical signals via neural-network-based multi-ODF fusion - Stasiak, Bartłomiej; Mońko, Jędrzej; Niewiadomski, Adam (Zielona Góra: Uniwersytet Zielonogórski)
The problem of note onset detection in musical signals is considered. The proposed solution is based on known approaches in which an "onset detection function" is defined on the basis of spectral characteristics of audio data. In our approach, several onset detection functions are used simultaneously to form an input vector for a multi-layer non-linear perceptron, which learns to detect onsets in the training data. This is in contrast to standard methods based on thresholding the onset detection functions with a moving average or a moving median.
Keywords: note onset detection; onset detection function; multi-layer perceptron; multi-ODF fusion; NN-based fusion